Formation of Regional and National Song Choirs as a Means of Strengthening National Identity for Students of Sanggar Guidance Permai, Pinang Malaysia - Setianingsih, Rofiqoh; Hanifah, Zulfa Izzah; Widyati, Feny Dwi; Wardani, Greshela Ayudya; Handayani , Lina (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
This research aims to introduce the cultural values ​​and traditions of the Indonesian nation and to increase the creativity and artistic talent of SB Permai Pinang children.This research uses action research methods which are collaborative and participatory in nature. Data collection techniques are carried out through observation and documentation. The data obtained was analyzed using qualitative analysis techniques. Data analysis was carried out descriptively to describe the process of forming regional and national song choirs, as well as their impact on strengthening the national identity of the students of Sanggar Guidance Permai Pinang. The results of this research were foundThe problem that can be concluded is first, students' lack of interest in national mandatory songs and regional songs. Second, there is a lack of material related to national culture. The results of observations showed that all the children there knew the song Indonesia Raya. 50% of the 44 SB students memorized the song lyrics, 40% forgot some of the lyrics and the other 10% did not memorize them. The main conclusion of this research is the need for concrete measures to strengthen national identity, especially among immigrant children. The formation of regional and national song choirs is an effective way to overcome the challenges of globalization and maintain Indonesia's cultural diversity.